Determinants of Tax Compliance Among Micro Food Businesses in Cavite, Philippines - Aeriel Louh Reign V. Banaag; Florindo C. Ilagan; Elizabeth D. Bigalbal; Dolores L. Aguilar; Maria Cristina L. Desepida; Jaysi T. Corpuz; Tricia Claire D. Apostol; Queen Aizaell P. Ramos; Princess Mae D. Tan; Nobel Victoria S. Cruz; Lyka Mae P. Quite; Hannah Nicole G. Valencia; Aeron Charles H. Casiño; Rowena R. Noceda (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The study focused on addressing existing gaps in the literature by examining the extent of perceived factors that influence the tax compliance of micro food businesses in selected areas of Cavite. It aimed to (1) determine the business profile of micro food businesses in selected areas of Cavite, (2) identify the level of perception of each of the perceived factors such as tax literacy and awareness, enforcement of tax laws, tax modernization, perception of the tax system, and cost of compliance, (3) examine the level of tax compliance, and (4) assess the effect of perceived factors on tax compliance of the participants. In this quantitative study, descriptive and explanatory research designs were used. The study utilized survey questionnaire answerable using a four-point Likert scale. A sample size of 385 was obtained using a proportionate stratified sampling technique, descriptive statistics and regression analysis were applied to interpret the collected data. Level of tax compliance, showed an overall mean of 3.19 and a standard deviation of 0.64. The determinants of tax compliance among micro food businesses in Cavite found that tax literacy, perceived enforcement of tax laws, tax modernization, perception of tax system fairness, and cost of compliance positively affects compliance. Findings revealed that tax literacy and awareness, improved implementation and enforcement of tax laws, enhanced tax system modernization, and the financial and procedural efforts associated with taxation significantly influence tax compliance among micro food businesses.